Deaths from acute drug reactions in Galician (Spain) Prisons (2001-2010) - D. Miguel-Arias; C. Pereiro-Gómez; A.M. Bermejo-Barrera; C. Vázquez-Ventoso; T. Rodríguez-Barca
Introduction and objectives: drug use is associated with multiple complications with an increase in morbidity, with death by acute drugs reactions (ADR) being the most serious. A large percentage of the prison population has problems associated with drug additions, and substance abuse is also a common internal problem of penal institutions, despite their control measures. The goal of this study is to analyse the prevalence of ADR in penitentiaries, deceased sociodemographic characteristics as well as the circumstances in which they are produced. Material and methods: All deaths by ADR between 2001-2010 in Galicia are studied, in particular, those deaths that took place inside prisons. Results: In the whole sample (n=510) male (90.6%), single (46.1%) with an average age of 35.8 and with a prevalent factor of long experience in drug abuse. Thirty seven of them died in Penal/Correctional Institutions, representing 7.3% of the total sample. The characteristics of this population subtype were similar to the total sample (average age: 34.7 years; 89.2% were males) but we found significant differences regarding the substances detected. Discussion: ADR is the most frequent cause of death among drug addict convicts in prisons. The pattern of the detected substances in the toxicological analysis as well as the socio-demographic characteristics can help to establish a higher risk profile and preventive measures.